Two phase transitions in (d(x2-y2)+is)-wave superconductors - Ghosh, A.; Adhikari, S. K. (Elsevier B.V., 1999)
We study numerically the temperature dependencies of specific heat, susceptibility, penetration depth, and thermal conductivity of a coupled (d(x2-y2) + is)-wave Bardeen-Cooper-Schrieffer (BCS) superconductor in the presence of a weak s-wave component (1) on square lattice and (2) on a lattice with orthorhombic distortion. As the temperature is lowered past the critical temperature T-c, a less ordered superconducting phase is created in d(x2-y2) wave, which changes to a more ordered phase in (d(x2-y2) + is) wave at T-c1. This manifests in two second-order phase transitions. The two phase transitions are identified by two jumps in specific heat at T-c and T-c1. The temperature dependencies of the superconducting observables exhibit a change from power-law to exponential behavior as temperature is lowered below T-c1 and confirm the new phase transition. (C) 1999 Elsevier B.V. B.V. All rights reserved.
Keywords: d(x2-y2) + is-wave superconductor; specific heat; susceptibility; thermal conductivity